Patient Age and Outcome in Ischemic Stroke - Gajurel, Bikram Prasad; Karn, Ragesh; Rajbhandari, Reema; Ojha, Rajeev (Journal of Nobel Medical College, 2022)
Background: Age is the most important prognostic factor in ischemic stroke. Thisstudy was carried out in patients with ischemic stroke to describe the association of age of the patients with stroke severity at presentation and at three months. Materials and Methods: The data, which were collected retrospectively from hospital records, we reanalyzed by using the Statistical Package for the Social Sciences (SPSS) version 26. Age was divided into younger (≤ 50 years) and older (> 50 years) based on standard definition. Age was also divided into younger (< 60 years) and older (≥ 60 years) based on the Senior Citizens Act of Nepal. The associations were analyzed by using Chi-square test. Results: One hundred and fifty-three patients were included in the study. The mean age of the patients was 60.9 years. There was no statistically significant association between baseline stroke severity and the age groups defined both ways. More younger patients had good outcomes (44.4% good outcome vs 25.6% poor outcome in patients ≤ 50 years, p= 0.03; 52.8% good outcome vs 31.6% poor outcome in patients < 60 years, p=0.02). More older patients had poor outcomes (74.4% poor outcome vs 55.6% good outcome in patients > 50 years, p = 0.03; 68.4% poor outcome vs 47.2% good outcome in patients ≥ 60 years, p= 0.02). Conclusion: There was no significant association between young and old patients and the baseline stroke severity; however, more younger patients had good outcomes compared to older patients at three months, the differences being significant.